Pengaruh Kualitas Pelayanan Dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Di Grand Laguna Hotel & Villa - Febyola Puspa Dewani; Enik Tri Afrika; Rayhan Gunaningrat (STIKes Ibnu Sina Ajibarang, 2024)
The purpose of conducting this research is to collect information that will be used to analyze the influence of service quality and customer satisfaction on customer loyalty at the Grand Laguna Hotel & Villa. And it is hoped that it can help companies solve the problems they face according to the topic chosen by the author, by analyzing, especially information and data regarding the influence of service quality and customer satisfaction on customer loyalty. In this research the method used is quantitative. The population in this study were all customers of the Grand Laguna Hotel & Villa. According to data from HRD Grand Laguna Hotel & Villa. The sample in this study was 66 respondents. The data analysis used is multiple regression analysis, multiple correlation, coefficient of determination f test and t test. There is a positive and significant influence of service quality on customer loyalty. There is a positive and significant influence of satisfaction on customer loyalty. Service quality and satisfaction together have a positive and significant influence on customer loyalty. The SPSS output results of the F test show that the calculated F value is 238,399, which is > 2,700 with a significant value of 0.000 < 0.05, so it can be concluded that service quality and customer satisfaction have a simultaneous influence on customer loyalty. Based on the T test results in the coefficients table, partial test results can be seen as follows. Service quality (X1) has a T count of 1.166 < T table 1.660, a large significance value of 0.247 > 0.05, so the service quality variable has no effect on customer loyalty. Customer satisfaction (X2) has a calculated T of 8.850 > T table of 1.660, a significance value of 0.000 < 0.05, so the customer satisfaction variable has a significant influence on customer loyalty. Customer satisfaction (X2) has a calculated T of 8.850 > T table of 1.660, a significance value of 0.000 < 0.05, so the customer satisfaction variable has a significant influence on customer loyalty.